A study on impact of receiving training on football and sprinting on body composition and physical fitness status of adolescent males - Banerjee, N.; Chatterjee, S.; Chaterjee, S.; Chatterjee, A.; Bhattacharjee, S.; Santra, T.; Saha, B.; Mukherjee, S.; Manna, I. (American Journal of Sports Science, 2014)
Physical characteristics and body composition have been known to be fundamental to excellence in athletic performance. Specific athletic events require different body types and weights for maximal performance. Therefore determination of body constitution and fitness status of an athlete is very important for producing maximal performance. With growth of children and adolescents there is a change in body composition parameters and the gender difference becomes more pronounced. Soccer playing and sprinting are the popular playing events. Both of them require fast body movements and therefore receiving training on these games may have some impact on body constitution and eventually on fitness status. A study was undertaken, in this backdrop, on randomly selected male adolescents of age range 12-18 years, receiving training in football (n1 = 36) and in sprinting (n2 = 32), the inclusion criterion being that the volunteers for the study should be receiving training for at least a period of 3 years with no chronic disease history. It has been observed that male adolescent individuals receiving similar pattern of training in football and sprinting did not vary significantly in terms of body composition but those being trained in football having better fitness status, compared to their sprinter counterparts.